Heat transfer simulation in an industrial furnace firing natural gas and pure oxygen for production of ceramic frits - Filho, Edemar Morsch [UNESP]; de Paulo Nicolau, Vicente; Seman, Laio Oriel; Possamai, Talita Sauter (Springer Nature, 2023)
This study covers the thermal simulation of an industrial furnace used to produce ceramic frits, a material requested for glazes and coatings of tiles and porcelains. The current production in the studied kiln is around 700 kg/h, and the furnace consumes around 1.0 MW by firing natural gas with pure oxygen. In this process, energy transfer by radiation is dominant, and species-like CO2 and H2O in the flue gas constitute a participant gas that interferes in the heat transfer. Eddy Dissipation Model, Weighted Sum of Gray Gases, and k- ϵ with a turbulence intensity of 5% are selected as models for combustion, absorption of participant media, and turbulence, respectively. A kinetic model WD 1-step is chosen for the reaction of CH4/O2 with a slight oxidizer’s excess. The combustion chamber and load domain are solved separately but coupled during iterations to improve stability and reduce computational cost. A simplified multiphase model is prescribed at the load based on thermodynamic properties as temperature functions. Experimental measurements of the furnace are used to validate numerical results. Two new positions of the chimney are proposed, and the furnaces’ performance is compared with the current operational model in the industry. Improvement in production is observed for a chimney in the front top of the furnace. With a chimney in the top back, the current case presents the second-best configuration tested, followed by the case with a chimney in the top center.
Keywords: Oxy-combustion; Participant media; Thermal radiation; Thermal simulation; Vitreous material